Penerapan Aplikasi Klasifikasi Hukum Tajwid Menggunakan Image Processing - Kindarya, Fabyan; Kusumaningtyas, Entin Martiana; Barakbah, Aliridho; Permatasari, Desy Intan; Al Rasyid, M. Udin Harun; Ramadijanti, Nana; Fariza, Arna; Syarif, Iwan; Sa'adah, Umi; Saputra, Ferry Astika; Ahsan, Ahmad Syauqi; Sumarsono, Irwan; Yunanto, Andhik Ampuh; Edelani, Renovita; Primajaya, Grezio Arifiyan; Kusuma, Selvia Ferdiana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Tajwid is an important science that regulates the way of reading the verses of the Al-Qur’an properly. Learning Tajwid means knowing the meaning that corresponds to the correct recitation. Learning to read the Al-Qur’an tends to be done traditionally in a place of learning or by calling a teacher to the house. Learning in this way has some drawbacks, such as the limited availability of trained and competent teachers because not all areas have sufficient access to these teachers. Dependence on schedules and locations can be a constraint for students with limited mobility or busy schedules. The role of the teacher is still important in learning tajwid, especially in providing effective explanations, guidance, and feedback. However, to overcome these shortcomings, integration with independent and technology-based learning methods can help improve the accessibility, flexibility, and quality of tajwid learning. The classification of tajwid laws using image processing allows users to see the results of inputting images of verses of the Al-Qur’an into the type of detected nun sukun tajwid and how to recite it. The initial stage of this system in detecting tajwid laws from uploaded images is the input of images by users, which can be done in two ways, namely by directly taking pictures using a smartphone camera or uploading images from the gallery. This is followed by the OCR process to detect the Arabic text contained in the image and provide diacritics for that Arabic text. Finally, letter classification is carried out after nun sukun and classification of tajwid laws contained in accordance with the detected letters after nun sukun. This system has an accuracy rate of 92.18% from the classification results that have been carried out.